Enzymatic hydrolysis and ethanol production using xyloglucanase and debaromyces hansenii from tamarind kernel powder: galactoxyloglucan predominant hemicellulose - Menon, Vishnu; Prakash, Gyan; Rao, Mala (Journal of Biotechnology, 2010)
The hydrolysis and ethanol production from tamarind kernel powder (TKP), a rich source of galactoxyloglucan (GXG) was investigated for the first time using xyloglucanase and thermotolerant Debaromyces hansenii. The acid hydrolysis of TKP with 2N H(2)SO(4) at 120 degrees C for 30 min yielded an overall saccharification of 94% based on the total available carbohydrate content and further fermentation at 40 degrees C with thermotolerant D hansenii produced an ethanol yield of 0.35 g/g. A maximum hydrolysis of 55 and 78% for GXG was obtained in 48 h at 50 degrees C using Thermomonospora xyloglucanase (TXy) and accellerase (TM) 1000, respectively. The synergistic effect of beta-galactosidase and xyloglucanase was demonstrated by the exogenous addition of beta-galactosidase to TXy which improved the overall hydrolysis of GXG by 30%. The rate of hydrolysis of GXG with TXy and accellerase was increased by 15-20% in the presence of chemical surfactants (tween 80 and toluene) or protein additive (BSA). The fermentation of enzymatic hydrolysates of GXG by TXy and accellerase with free cells at 40 degrees C produced an ethanol yield of 0.39 and 0.41 g/g whereas with immobilized cells produced 0.45 and 0.43 g/g, respectively, with a theoretical conversion efficiencies of 78-88%. The immobilized yeast cells were reused six times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Galactoxyloglucan; Hydrolysis; Tamarind kernel powder; Thermotolerant yeast; Xyloglucanase